Survey 0n Chatbot Work and Design - Singh, Nidhi; Mittal, Kajol (International Journal of Computer Sciences and Engineering, 2025)
The computer program that talk to human in natural simple language is called a Chatbot. Chatbots are intelligent, conversational software or software agents that takes input in the form of text and voice. They provide the response of the input in the form of output. The chatbot software technology was developed in the 1960’s. Now the chatbot easier to train and implement. It is an open source code, so its development platform is widely available. It is used to improve customer understanding and supporting learning. These paper presentation analysis about chatbot. The paper discusses about different Chatbots on different technology and uses in different areas.